Six‐Photon Excited Self‐Trapped Excitons Photoluminescence in Lead‐Free Halide Perovskite. Issue 5 (23rd December 2022) - Jiang, Jutao; Niu, Guangming; Sui, Laizhi; Wang, Xiaowei; Zeng, Xiangyu; Zhang, Yutong; Che, Li; Wu, Guorong; Yuan, Kaijun; Yang, Xueming
Abstract: Multiphoton absorption (MPA) effects are suitable for biophotonic applications due to the long penetration depth and high spatial confinement. Compared with lead halide perovskites, relevant studies on MPA effects of lead‐free perovskites are still scarce, especially for the high‐order MPA effects. Herein, an all‐inorganic lead‐free Cs2 TeCl6 perovskite crystal is reported that exhibits three‐ to six‐photon absorption (3PA to 6PA) effects over a wavelength range of 800–2200 nm. The results of steady and transient optical experiments indicate that the single‐ and multiphoton excited broadband orange emission in Cs2 TeCl6 crystals is attributed to the self‐trapped excitons (STEs) recombination. What is more, the 6PA cross‐section (δ6 ) has been determined to be 1.87 × 10 −174 cm 12 s 5 photon −5 (at 1980 nm). As far as it is known, the high‐order 6PA effect is unprecedented in lead‐free perovskites, which paves the way for the future development of lead‐free perovskite high‐order multiphoton application. Abstract : The unprecedented high‐order six‐photon absorption (6PA) effect is observed in lead‐free perovskites. Multiphoton‐excited time‐resolved photoluminescence (PL) suggests that multiphoton PL of Cs2 TeCl6 crystals is ascribed to the recombination of self‐trapped excitons.